Peran Ibu Dalam Penanganan Stunting - Donal Nababan; Siska Evi Martina; Fatimah Azhari; Vita Rahmadayanti (Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2023)
Stunting is a type of infant growth retardation (stunting) caused by prolonged inadequate food intake due to the provision of food that does not meet nutritional needs. Stunting can occur while the fetus is still in the womb and does not occur until the child is two years old. It is generally caused by food intake that does not meet nutritional needs. Various efforts are being made by government agencies. Upon investigation, it was discovered that there were gaps in stunt processing, resulting in a continuous increase in stunt processing that never stopped. This gap is reflected in the daily life of stunted children, the way mothers treat them. The role of mothers is one of the key issues in dealing with stunting. One of her efforts is to provide education for mothers of stunted children. General goals: Expand mothers' knowledge of balanced nutrition for children and raise awareness among mothers about keeping their children healthy. Special: Reduces stunting, prevents stunting from an early age and promotes a clean and healthy lifestyle. The survey method is a compound survey, that is, a method of combining quantitative and qualitative surveys and conducting interviews with informants. Conducted in Bahari sub-district, Belawan 1 sub-district, Belawan II sub-district and Baganderi sub-district. The number of informants for this study was 77, of whom a total of 77 were mothers of stunted children.